Khawaja Gulam Farid and Philosophy of Sufism: Exploring the Mystical Teachings of Khawaja Gulam Farid (Journal of Advances and Scholarly Researches in Allied Education, 2019)
KÍwjw Zulwm rId dy sUI kwiv AMdr ierwn’c ivkisq hoey ielmy-qs`vu dy Jlkwry swP dyKy jw skdy hn, jo SIAw ieslwm dI SrIAq Aqy qrIkq qoN is``Dy rUp iv`c pRBwivq irhw hY[ h`Qly prcy iv`c AsIN qs`vu ws is`DWq nUry-muhMmd nUM AwDwr bxw ky KÍwjw swihb dy kwiv iv`cly qs`vu dy ielm nUM idRStIgocr krn jw rhy hW[ SIAw smudwie iv`c ivSvws sI ik sMswr dI isrjxw qoN pihlW ie`k AlOikk nUr mOjUd sI, ijsnUM udw ny Awpxy nUr qoN pYdw kIqw, iehI nUry-muhMmdI sI[ ieh nUr dUjy pYgMbrW qoN cldw hoieAw hzrq muhMmd qoN bwAd SIAw iemwmW iv`c pirivSt hoieAw[ ieh nUr pYgMbrW Aqy iemwmW nUM pwpW qoN bcwauNdw, “mwsUm” bxwauNdw Aqy AlOikk rh`sW dw igAwn pRdwn krdw hY[ jo ienswn r`bI igAwn hwisl krnw cwhuMdw hY, auh pYgMbr dI pYrokwrI AiqAwr kry Aqy iemwmW dy zrIey ielwhI nUr nwl juVy[1 ies nUr nMU hkIkqy-muhMmdI vI ikhw jWdw hY[ sUIAW iv`c islislAW dI irvwieq iesy is`DWq au`pr AwDwirq hY[